Das passarelas às práticas de consumo: Uma análise dos discursos da marca de moda de luxo Balenciaga - Bucker, Luiza Bonassa (2025)
Contradicting the common notion that reduces advertising to a mere instrument of mass manipulation, this research starts from the principle that the consumption of goods is a complex symbolic system, with fashion being one of the most eloquent mechanisms of social significance. In the luxury sector, this phenomenon takes on even more striking contours, revealing changes that have redefined the relationship between people and objects, from modernity to the hyperconnected world. In this context, traditional brands face the challenge of successively reinventing themselves, operating in fields of dispute where different narratives compete for the construction of meanings based on social values. This research aims to analyze the discursive transformations of Balenciaga, investigating how the brand mobilizes discourses and creates advertising force lines to translate and reinvent existing consumption narratives, ensuring its relevance and distinction throughout its history. The object of study focuses on three distinct creative moments of the brand: Cristóbal Balenciaga (1938-1968), Nicolas Ghesquière (1997-2012), and Demna Gvasalia (2015-2024). The analyzed corpus encompasses advertisements, editorials, and fashion shows representative of each period. The theoretical framework adopts a multidisciplinary approach that integrates French Discourse Analysis (Maingueneau, Orlandi, Foucault), structural analysis of advertising (Carrascoza), consumption theories (Lipovetsky, McCracken), the brand identity model (Semprini), among others. The results reveal Balenciaga as a translator of its time: Cristóbal articulated the emergence of the modern urban woman, Ghesquière of the globalized cosmopolitan woman, and Gvasalia of the hyperconnected subject. We understand that, paradoxically, the more contemporary luxury questions its foundations, the more it reaffirms its mediating function, transforming criticism of consumption into sales discourse. The question arises: wouldn't contemporary luxury be tautological?